A Current Panoramic Vision on Autobiographical Literature (ALPHA. Journal of Arts, Literature and Philosophy, 2003)
This article, on the one hand, sets forth an overall view about the most important theoretical and critical approaches to autobiographical literature. On the other hand, it presents a summary on current research on autobiographical literature. It analyzes trends in Chilean autobiography in relation to globalized concerns, based on forms of self-depiction and an analysis of literary memoirs.
Keywords: autobiographical literature; Chilean literature; memory; narration